Publish or perish : scheduling challenges in the publishing industry - Drake, Matt (Matthew J.); Klingenberg, Beate; Gavin, David (Pearson, 2014)
This new business analytics case study challenges readers to manage the complex book publishing process from manuscript through printing and shipping, keeping projects on time to meet the industry's crucial spring and fall seasons. Crystallizing realistic analytical challenges faced by companies in many industries and markets, it exposes readers to the entire decision-making process, providing opportunities to perform analyses, interpret output, and recommend the best course of action. Author: Beate Klingenberg and David Gavin, Marist College.